An investigation into the performance of vegetated biofilters in removing nutrients from stormwater in the City of Cape Town, South Africa - Milandri, Stefan (Department of Environmental and Geographical Science, 2015)
In 2009, the City of Cape Town (CoCT) adopted a stormwater policy which mandates that new and existing developments should reduce the concentrations of phosphorus and suspended solids in stormwater runoff by 45% and 80% respectively, but offered no explicit guidance about how these water quality targets might be achieved. This study aims to contribute to the limited knowledge that exists about the performance of local plant species to treat stormwater.